Seed Quality Assurance System through Participatory Guarantee System - Centre for Sustainable Agriculture (2023)
The Participatory Guarantee Scheme (PGS) is an integral component of a decentralized, farmer-led seed system that aims to empower farmer groups with the collective authority to validate the standards of truthfully labeled seeds (TLS). Mainstream seed certification procedures require a licensed seed officer to verify the quality of seeds in accordance with the Indian Minimum Seed Standards and provide certification. Several farmers, especially smallholder and women seed producers, might not be able to adhere to or afford the stringent requirements of formal certification procedures. These marginalized farmers might also struggle to obtain the necessary agri-inputs to meet the standards laid down by mainstream seed certification procedures. Hence, a trust-based quality assurance approach to seed authentication that is farmer-led is likely to benefit them.